Prostatic Abscess on Xanthogranulomatous Prostatitis: Uncommon Complication of an Uncommon Disease - Youness Jabbour; Hamza Lamchahab; Sumba Harrison; Hafsa El Ouazzani; Tarik Karmouni; Khalid El Khader; Abdellatif Koutani; Ahmed Iben Attya Andaloussi (Case Reports in Urology)
Xanthogranulomatous prostatitis is a rare benign inflammatory process of the prostate. Only few cases have been reported in the English literature. Xanthogranulomatous prostatitis is usually an incidental finding after needle biopsy or transurethral resection of the prostate in patients suffering from low urinary tract symptoms. We report the case of a 59-years-old patient diagnosed with prostatic abscess managed by transurethral resection of the prostate. Histopathological examination of resected prostatic tissue revealed abscessed xanthogranulomatous prostatitis with no evidence of malignancy. Xanthogranulomatous prostatitis presenting as a prostatic abscess is a rare finding. To the best of our knowledge our case represents the fourth case of xanthogranulomatous prostatitis presenting as prostatic abscess reported in the English literature so far.